La demanda de televisión digital terrestre en el Perú - Sanabria Montañez, César (2009)
The technological development in the communications will be allowing a major level of access to the information and communication, in it there registers the adoption of a standard of digital terrestrial television (TDT) in Peru, which turns into an opportunity to improve the development of our society. This way then, the present study shows the relation that exists between technology and development from the perspective of access to the TDT and the characteristics of the TDT; likewise it indicates that 3 of every 4 homes in Peru it is ready to be TDT's demand; but that the bounding ones of poverty indicate that in order that it should exist a real demand of the equipments that allow to catch the TDT will be necessary a form of state subsidy.